2011
DOI: 10.1002/lt.22324
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of supplementation with branched-chain amino acids on postoperative bacteremia in living donor liver transplant recipients

Abstract: The aim of this study was to investigate the effects of preoperative oral supplementation with branched-chain amino acids (BCAAs) on postoperative bacteremia after living donor liver transplantation (LDLT) for chronic liver failure. Two hundred thirty-six patients who underwent adult-to-adult LDLT were evaluated in this retrospective study. The patients were divided into 2 groups: those who received oral supplementation with BCAAs before transplantation (the BCAA group; n ¼ 129) and those who did not (the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 30 publications
0
34
0
2
Order By: Relevance
“…Kawamura et al [99] reported that early interventional oral BCAAs might prolong the liver transplant waiting period by preserving hepatic reserve in patients with cirrhosis. A retrospective analysis also showed that BCAA treatment before LDLT may reduce the incidence of posttransplant bacteremia [100] .…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Kawamura et al [99] reported that early interventional oral BCAAs might prolong the liver transplant waiting period by preserving hepatic reserve in patients with cirrhosis. A retrospective analysis also showed that BCAA treatment before LDLT may reduce the incidence of posttransplant bacteremia [100] .…”
Section: Liver Transplantationmentioning
confidence: 99%
“…In patients undergoing living donor liver transplantation, perioperative administration of the same BCAA-enriched mixture has been demonstrated to improve metabolic status [17] and reduce the incidence of bacteremia [18].…”
Section: Clinical Evidencementioning
confidence: 99%
“…The right lobe graft was procured using a typical method described elsewhere [1, 11, 12, 13, 14]. The actual graft weight was 546 g, which accounted for 50.4% of the recipient's standard liver volume.…”
Section: Case Reportmentioning
confidence: 99%
“…The drained ascites was below 500 ml/day and all abdominal drains were removed by postoperative day 6 except for the biliary stents (table 1). Other than the renal replacement therapy and dose modulation of renal excretory drugs such as acyclovir, the perioperative management of the recipient was typical, as previously described [1, 11, 12, 13, 14]. Immunosuppression was induced with intravenous methylprednisolone and then switched to oral prednisolone, cyclosporin A and mycophenolate mofetil.…”
Section: Case Reportmentioning
confidence: 99%